The Relationship between Impulsive Behavior and Nomophobic Tendencies in Students in Makassar City - Sri Dewi Saputri; Sitti Murdiana (Polteknik Ilmu Pemasyarakatan, 2023)
The development of technology with the rise of social media applications on smartphones makes students easier and more comfortable in carrying out various activities. The convenience of these features encourages students to use smartphones unwisely so that they will experience feelings of anxiety when away from smartphones known as nomophobia tendencies. The purpose of this study was to determine the relationship of impulsive behavior to nomophobia tendencies in students in Makassar City. The method in this study is quantitative correlation with the Spearman rho test. This study involved students in Makassar City who have more than one social media application aged 18-25 years using incidental sampling technique. The results in this study indicate that there is a positive relationship between impulsive behavior and nomophobia tendencies in students in Makassar City with a correlation coefficient of 0.504 with a significance level of 0.000. The results of additional analysis also show that the nomophobia tendency variable has a relationship based on the duration of social media use, the frequency of social media use, and the number of social media applications. The implication of this study is the need for students to set limits in using smartphones for positive aspects in life.